Physicochemical and structural properties of meat analogues from yeast and soy protein prepared via high-moisture extrusion. (15th February 2023) - Xia, Songgang; Shen, Shuo; Song, Jian; Li, Ku; Qin, Xianwu; Jiang, Xiaoming; Xue, Changhu; Xue, Yong
Highlights: This is the first study of producing meat analogues with yeast protein. Yeast protein can improve the fibrous structure of meat analogues. Yeast protein makes meat analogues brighter and whiter. The β-sheet structure content is the highest with 40 g/100 g yeast protein content. Abstract: In this study, yeast and soy protein at different ratios (0:1, 1:9, 2:8, 3:7, 4:6, and 5:5) were used to produce meat analogues (MA) via high-moisture extrusion. According to color analysis, the addition of yeast protein (YP) increased the lightness of MA from 43.12 ± 0.26 (the control) to 50.37 ± 0.46 (50 g/100 g, dry basis). Textural results indicated that when the YP content was 40 g/100 g (dry basis), the hardness, chewiness, and fibrous degree of MA reached the maximum (523.94 ± 11.91 N, 724.55 ± 22.89 N, and 2.06 ± 0.15, respectively), which were higher than the control (419.63 ± 7.52 N, 618.02 ± 14.82 N, and 1.43 ± 0.03, respectively). Furthermore, YP increased the free water ratio, SS bond, and total β-sheets structure content, while reducing the β-turn structure content and thermal stability of MA. Overall, YP is a promising protein source for preparing high-quality MA.